2006
DOI: 10.1002/ange.200602488
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of Methanol‐to‐Olefin Conversion at Zeolites with Systematically Selected Framework Structures

Abstract: Genauer Blick: Der so genannte Kohlenwasserstoffpool‐Mechanismus funktioniert bei der Umwandlung von Methanol in Olefine (MTO‐Prozess) am Zeolith ZSM‐22 wegen der engen Gerüstkanäle (0.57 nm) nicht. Dafür bot dieses System die Möglichkeit zu genauen mechanistischen Studien ohne Störung durch Sekundärreaktionen. Die dabei erhaltenen H/D‐Austauschmuster von Toluol sprechen für einen Schälmechanismus (paring mechanism).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…[1] A breakthrough in the mechanistic understanding of the MTH reaction was the formulation of the "hydrocarbon pool mechanism" by Dahl and Kolboe, [2,3] which postulates that methanol is continuously added to aromatic reaction centers, from which light alkenes are split off in later reaction steps. Herein, we report studies of the MTH reaction over ZSM-22 at a wider range of reaction conditions and demonstrate that the previous conclusions [7][8][9][10] are not universally valid. [5,6] ZSM-22 (TON) is less well studied [7][8][9][10] as a MTH catalyst.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…[1] A breakthrough in the mechanistic understanding of the MTH reaction was the formulation of the "hydrocarbon pool mechanism" by Dahl and Kolboe, [2,3] which postulates that methanol is continuously added to aromatic reaction centers, from which light alkenes are split off in later reaction steps. Herein, we report studies of the MTH reaction over ZSM-22 at a wider range of reaction conditions and demonstrate that the previous conclusions [7][8][9][10] are not universally valid. [5,6] ZSM-22 (TON) is less well studied [7][8][9][10] as a MTH catalyst.…”
mentioning
confidence: 79%
“…The MTH reaction proceeds over Brønstedacidic zeolite or zeotype catalysts, and near-commercial processes exist for the methanol-to-gasoline (MTG) reaction over ZSM-5, as well as the methanol-to-olefin (MTO) reaction over A breakthrough in the mechanistic understanding of the MTH reaction was the formulation of the "hydrocarbon pool mechanism" by Dahl and Kolboe, [2,3] which postulates that methanol is continuously added to aromatic reaction centers, from which light alkenes are split off in later reaction steps. [11] Song and co-workers [7][8][9] reported the failure of ZSM-22 to convert methanol into olefins. [5,6] ZSM-22 (TON) is less well studied [7-10] as a MTH catalyst.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Just recently, Cui et al have reported experimental evidence for transition-state-shape selectivity in studies of methanol-to-olefin conversion on zeolites with varying pore size. [18] Experimental claims to transition-state-shape selectivity are, ideally, verified by theoretical methods, [19][20][21] since these are more suited for elucidating the extent to which the local shape of the pore influences local reaction rates. To the best of our knowledge, ours is the first theoretical study on the hydrocarbon-pool proposal to take topological concepts explicitly into account, by focusing on both the electrostatic stabilization and geometrical constraints of typical zeolite frameworks on key carbenium ions and transition states.…”
mentioning
confidence: 99%